Mejoramiento del Canal de riego Quebrada Honda Pashul, Caserios Paraiso y Palambe, Distrito de Sallique-Jaen-Cajamarca - Moya Delgado, José Kristian (2016)
Present research paper, entitled "Improving channel broken irrigation honda Pashul, Caserios Paraiso and Palambe, district Sallique-Jaen-Cajamarca", aims to design a suitable geometrical section for the raceway and structures therein comprising (Deposits- Desander, Safety Inspection, stilling pool, Craps concrete Buzonetas, Partidor and pipe). The design criteria are supported in their mathematical calculations, enabling a hydraulically efficient and structurally secure infrastructure thus ensure good operation and availability of water resources to agricultural land. For project development office software and different engineering programs applied as H-channels, AutoCAD, AutoCAD Land and S10 were used. In the annexes, the study of water supply and demand, rising channel topography, location map, floor profiles, artwork, metrados, general budget, unit costs and resource scheduling work will be included. The study of the area served by the project or target area is performed based on the surface corresponding to the town that are within the project area, in our case Caseríos "Palambe, El Porvenir and Pashul" project in which It was taken as the main material PVC pipe due to difficult access for hauling material and the constant landslides in the area, plus the flow was obtained both agricultural supply needs and the population consumption.